America & Islam: soundbites, suicide bombs and the road to Donald Trump - Pintak, Lawrence (I. B. Tauris, 2019)
"Donald Trump's first term as the 45th President of the United States of America has shocked the world. His attitudes towards Islam became a key point of contention on the campaign trail, and in power Trump has continued his war of divisive words and deeds. Here, acclaimed journalist Lawrence Pintak scrutinizes America's relationship with Islam since its foundation. Casting Donald Trump as a symptom of decades of misunderstanding and demonization of the Islamic world, as well as a cause of future tensions, Pintak shows how and why America's relationship with the world's largest religion has been so fractious, damaging and self-defeating. Featuring unique interviews with victims and perpetrators of Trump's policies, as well as analysis of the media's role in inflaming debate, America & Islam seeks to provide a complete guide to the twin challenges of terrorism and the polarizing rhetoric that fuels it, and sketches out a future based on co-operation and the reassertion of democratic values--"Bloomsbury Publishing